Ihsan al-Taqrib fi Sharh al-Tahrir, by Imam Muhammad Abd al-Ra’uf al-Manawi al-Haddadi (952 AH - 1031 AH) (may God have mercy on him) - Ahmed Abd Jassim, (Islamic Sciences Journal, 2024)
ABSTRACT The research dealt with paintings from a manuscript on Shafi’i jurisprudence by Sheikh Abdul Raouf Al-Manawi, and the content of these paintings from the manuscript was on the issue of marriage and the guardian’s guardianship, as God Almighty preserved this religion and preserved its components, including man, as he decreed for him everything that maintains permanence and survival for humanity, including offspring. Al-Bashri, where I studied the author’s personal life and his method in compiling this blessed book, and I investigated and studied the book on marriage up to the saints’ chapter, and I concluded this research with a conclusion in which I mentioned the most important results I reached, and the recommendations that I saw serve society and the general good of Muslims, and finally I ask God May God Almighty make this work of mine sincere for His noble face, so whatever slips are from me and from Satan, and whatever is obstructed is by the grace of God Almighty.